Strategic Management Analysis of Social and Environmental Responsibility (SER) in Improving Community Welfare at PT Sinergi Gula Nusantara, Glenmore Sugar Factory Unit - Risa Nur Wahyuni; Meirinawati M; Eva Hany Fanida; Neny Ayu Nourmanita (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Social and Environmental Responsibility (TJSL) is an obligation for State-Owned Enterprises (BUMN) to support sustainable development and improve community welfare. PT Sinergi Gula Nusantara Glenmore Sugar Factory Unit has implemented various TJSL programs in the fields of social, education, health, and environment. However, the implementation still faces challenges such as uneven program distribution and limited community participation. This study aims to analyze the strategic management of TJSL in improving community welfare. This study uses a descriptive qualitative approach. Data collection techniques include interviews, observations, and documentation. Data analysis applies strategic management theory to examine the planning, implementation, and evaluation of TJSL programs. The results show that TJSL strategies have positively impacted the community, including improved economic welfare, job creation, and enhanced social and environmental quality. However, the effectiveness of the programs is not yet optimal due to limitations in program distribution and community participation. Therefore, strengthening strategic planning, increasing community collaboration, and continuous evaluation are needed to ensure more targeted and sustainable TJSL programs.